High oxide ion conductivity in layer-structured Bi4Ti3O12-based ferroelectric ceramics. Issue 29 (1st July 2019) - Long, Changbai; Ren, Wei; Li, Yiwen; Liu, Laijun; Xia, Yuanhua; Fan, Huiqing
Abstract : B0.97 T0.73 Mg0.02 shows high oxide ion conductivity, which is comparable to that of other leading solid oxide electrolyte materials. Abstract : The layer-structured perovskite Bi4 Ti3 O12 is a well-known lead-free ferroelectric and piezoelectric material with potential applications in both non-volatile memory devices and high-temperature sensors. In this paper, high oxide ion conductivity is observed for modified Bi4 Ti3 O12 -based ceramics, and their associated oxygen transport mechanism is investigated systemically. Impedance data and dc conductivity as a function of oxygen partial pressure reveal that Bi4 Ti3 O12 shows mixed oxygen ion and hole conduction. Bi deficiency in the starting composition leads to no change in the conduction mechanism and no significant increase in bulk conductivity ( σ b ). Interestingly, high oxide ion conductivity is achieved with further Mg 2+ acceptor doping at the B site. The optimum composition with a nominal formula of Bi3.88 Ti2.92 Mg0.08 O11.74 exhibits a high σ b of ∼10 −2 S cm −1 and a high ionic transport number ( t ion ) of ∼0.92 at 650 °C, which are well comparable to those of leading solid oxide electrolyte materials. Furthermore, this composition shows extremely low conductivity degradation at 450 °C, 600 °C and 700 °C. The present work opens up new horizons for Bi4 Ti3 O12 as an oxide ion conductor in addition to ferroelectric- and piezoelectric-based applications.